The Needs for Information and Education Media in Supporting Self-Management of Patients with Diabetes Mellitus - Rapitos Sidiq; John Amos; Widdefrita Widdefrita; Novelasari Novelasari; Evi Maria Silaban; Yannurdin Yannurdin; Suhaimi Suhaimi; Mahaza Mahaza (Media Kesehatan Masyarakat Indonesia, 2020)
Diabetes mellitus is a chronic disease that has a very high morbidity and mortality rate. This disease cannot be cured but can be controlled with good self-management. This research supports the need for appropriate information and educational media in supporting the self-management of patients with diabetes mellitus. This research is qualitative and quantitative. The sample of this study was 105 people with diabetes. Data collection was conducted from July to November 2019 at 7 Puskesmas in Padang City, namely: Nanggalo, Lapai, Alai, Andalas, Ambacang, Kuranji, and Pauh, with interview questions and interviews. Qualitative data processing techniques with coding and data validity by triangulation and analyzed using data reduction, data presentation, and analysis. Quantitative data analysis uses SEM (Structural Equation Model) analysis with the Lisrel 8.7 program. The results showed that the informants were elderly (56-65 years), 60% had good self-management quality, 65% actively participated in chronic disease management programs, 49.5 did not have cellphones. All aspects of self-management, namely blood sugar testing, physical exercise, taking medicine, diet and health education, can be used as educational material. Research information shows the fact most still need information about self-management of diabetics and in the form of conventional media. Informants who use phones that are approved for Android-based self-management applications.